Language Policy of Higher Education Institutions in the European Union as a Tool for Internationalization - Kupchyk, Larysa; Litvinchuk, Alona (Educological discourse, 2026)
The article analyzes the language policy of higher education institutions (HEIs) in the European Union (EU) within the context of internationalization processes, understood as the integration of international, intercultural, and global dimensions into the goals, functions, and delivery of educational services. The methodological framework of the study is based on the concepts of J. Knight, H. de Wit, and R. Villares, as well as on EU legal and policy documents. The article employs methods of systemic, comparative, and discourse analysis to identify the interrelation between language policy, internationalization, and the quality of higher education. It is established that language policy serves as a key instrument for implementing internationalization strategies, as it defines the languages of instruction, communication, administration, international programs, and the provision of language support for participants in the educational process. The analysis of EU countries’ experience (Spain, the Netherlands, and Italy) demonstrates that the development of English-medium programs, policies supporting multilingualism, and the formation of linguistic competence among staff and students are the main directions of university language policies. At the same time, attention is drawn to the risks associated with the dominance of the English language, which may lead to the marginalization of national languages and the loss of cultural specificity. The paper outlines the main functions of language policy: ensuring access to education for international students, supporting mobility and international cooperation, shaping the university’s image as a globally oriented institution, and promoting multilingualism and intercultural interaction. It is shown that effective language policy enhances the competitiveness of HEIs, improves the quality of teaching and research, expands opportunities for academic mobility, and fosters inclusion. The conclusions emphasize that a successful language policy of EU higher education institutions should balance global and local values, ensuring equilibrium between internationalization and the preservation of national linguistic identity. It should be integrated into universities’ strategic documents, supported by appropriate resources, language assistance, and systematic monitoring of outcomes. Language policy is thus viewed not merely as a regulatory tool but as a catalyst for global openness, academic excellence, and sustainable institutional development.